The balance of power in closely held corporations - Morten Bennedsen; Daniel Wolfenzon (Copenhagen Business School (CBS), Department of Economics, 1999)
We analyze a closely held corporation characterized by the absence of a resale market for shares and by potentially having several significant shareholders. The founder of the firm may optimally choose to distribute voting power to several large shareholders since this forces them to form coalitions to obtain control. A coalition, by grouping the cash flows of its members, internalizes to a larger extent the consequences of its actions and hence takes more efficient actions than its individual members. The model has other implications for the ownership structure of a closely held corporation: A one-share-one-vote rule improves efficiency; the optimal ownership structure has either one dominant shareholder or several equal-sized shareholders; and finally, efficiency decreases with the number of significant shareholders.
hdl:10398/7622
Keywords: G32; G34; 330; Closely held corporations; Ownership structure; Control dilution; Control coalition; One share - one vote